Análisis de la selección de sustrato por parte de Dendrophylax lindenii (Orchidaceae) en Cabo San Antonio , Península de Guanahacabibes, Pinar del Río, Cuba - Mújica, Ernesto; Raventós, Josep; González, Elaine (Lankesteriana: International Journal on Orchidology, 2013)
In this study we analysed the host-tree preference by the epiphytic orchid Dendrophylax lindenii in Cabo San Antonio, Península de Guanahacabibes, Cuba. We surveyed two transects of 1000 metres and variable widht, according to the topography. We noted the presence of the orchids and number counted all the individuals as well as the DBH at the insertion point of this orchid on the phorophytes and the height of trees in the semi-deciduous forest. We recording 344 individuals on 19 species of host tree (phorophyte).D. lindenii shows generalist behaviour on habitat selection, diameter and height insertion on host trees. The orchid was mainly found on Comocladia dentata, Diospyros crassinervis and Cedrela odorata. More than 54,4% of the D. lindenii were found on Comocladia dentata (24,4%), Sideroxylon foetidissimum (10,8%), Diospyros crassinervis (9,9%) y Tabebuia angustata (9,3%). Conservation effort should include the conservation of trees that are most frequently phorophyte of the orchid, especially the two species of trees which have commercial value, D. carsinervis y C. odorata.